Acceleration of Ocean Acidification in the Western North Pacific. Issue 22 (16th November 2019) - Ono, Hisashi; Kosugi, Naohiro; Toyama, Katsuya; Tsujino, Hiroyuki; Kojima, Atsushi; Enyo, Kazutaka; Iida, Yosuke; Nakano, Toshiya; Ishii, Masao
Abstract: Because annual anthropogenic CO2 emissions have grown rapidly over the past decades, there is a concern that anthropogenic CO2 invasion into the ocean may also have caused the rate of ocean acidification to increase. Here, we report the decadal and longer‐term variability in the rates of change of inorganic carbon variables since the early 1980s in surface seawaters of various oceanic regions along the 137°E repeat line in the western North Pacific. In the subtropical frontal zone, we found that the mean rate of acidification tracked the acceleration of the atmospheric CO2 increase; during 2008–2017, the rate of acidification was 30% faster than during 1983–2017. In the Kuroshio Recirculation and tropical zone, acidification trends were clear, but the trends were modulated by decadal variability associated with temporal variability in regional ocean circulation. Plain Language Summary: By taking up about 30% of the CO2 emitted by human beings, the ocean plays an important role in mitigating global warming. Modulation of the distribution of different forms of dissolved inorganic carbon in seawater causes another problem called "ocean acidification, " when excess CO2 enters seawater. Recent increases in the rates of anthropogenic CO2 emissions may have led to acceleration of ocean acidification. Analysis of data from shipboard measurements made from the subtropics to the tropics in the western North Pacific revealed that acidification of surface seawater from the subtropics to just south of Japan has been occurring over the last 35 years at the same rate as expected from the increase of atmospheric CO2 . Furthermore, in part of the subtropics, the acidification rates in recent decades have tracked the acceleration of atmospheric CO2 and have therefore been growing. In other regions, it is unclear whether there has been an acceleration of ocean acidification, likely because decadal‐scale changes in the regional ocean circulation make it difficult to evaluate the ocean acidification rate. The implication is that changes in regional ocean circulation that may have been caused by climate change may modulate the rate of ocean acidification in the coming decades. Key Points: The rate of ocean acidification has been increasing in recent decades in the subtropical western North Pacific along the 137°E meridian In its subtropical frontal zone, the increase in the rate of ocean acidification has been consistent with the rise of atmospheric CO2 In other regions, such as the Kuroshio Recirculation, the rate of ocean acidification may have been modulated by regional ocean circulation